Contemporary landscapes : in mixed media - French, Soraya (London : Batsford, 2017)
A great guide for painters who want to experiment with mixed media and make their landscape paintings more adventurous. Popular artist and teacher, Soraya French, encourages readers to experiment with mixing media and to create more adventurous paintings and broaden their artistic horizons. The media that Soraya uses in this book are acrylics, pastels and collage and she shows how to bring the best out of mixing these media with handy tips, some simple projects and several step-by-step demonstrations.
Includes index.
"Acclaimed artist Sorya French reveals the secrets of her stunning mixed-media landscape paintings, with tips on composition, technique, colour and texture. ; Discover how to use the wide range of art media available today, including more unusual materials such as glass bead gel and interference colours. ; Both practical and inspirational, this is the perfect book for anyone who wants to take their landscape painting in new and exciting directions."-- Back cover.
Keywords: French, Soraya; Mixed media painting -- Technique; Landscape painting -- Technique